Social, political and economic factors of architectural modernity in El Salvador - Cornejo Mejía, Cristina Maricela (Realidad, Revista de Ciencias Sociales y Humanidades, 2017)
Which are the buildings that we define as Modern Architecture in El Salvador? The word “modern” in architecture has a meaning and period in time that differs to the term coined by the general public, where it is usually points out the characteristics of a building of recent construction and with a particular aesthetic of formal finishes, according to the tendencies of the current market. So how is Modern Architecture in El Salvador? Where is it? In the history of El Salvador this period is defined between 1940 and 1980, where the meaning of the design of the buildings during this time was radically transformed. The aspects that drove this change are directly linked to the economic situation (bonanza periods), socio-political (military governments), technological (industrialization) and cultural (cinema, radio and television redefined social life). Realidad: Revista de Ciencias Sociales y Humanidades No. 150, 2017: 41-64